Abrasion-resistant composite layer and preparation method thereof

By designing a gradient structure and adding wear-resistant particles in the zinc-ferroalloy plating layer, the problem of not resistant to corrosion and not resistant to wear in high temperature and high humidity environments in the prior art is solved, and the high wear resistance and corrosion resistance of the composite layer are achieved.

CN119900060AActive Publication Date: 2025-04-29JIANGDONG FITTINGS EQUIP +1
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
CN202510317111.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-04-29
Estimated Expiration
2045-03-18

AI Technical Summary

Technical Problem

In the prior art, zinc-ferroalloy coating is neither corrosion-resistant nor wear-resistant in high temperature, high humidity, high chlorine and strong wind environments, and the particle content in the composite layer is limited, resulting in limited improvement in wear resistance.

Method used

Using a gradient structure design from the surface and the inner layer, Zn-Fe in the first zinc-iron composite layer has an η phase, and Zn-Fe in the second zinc-iron composite layer has a γ phase, and wear-resistant particles are added to both layers to improve the hardness and wear resistance of the composite layer.

Benefits of technology

The composite layer is excellent wear resistance and corrosion resistance under abrasive conditions, and the hardness and tribological properties of the composite layer are significantly improved through the use of wear-resistant particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119900060A_ABST
    Figure CN119900060A_ABST
Patent Text Reader

Abstract

The invention provides an abrasion-resistant composite layer and a preparation method thereof. The anti-abrasion composite layer comprises a passivation layer, a first zinc-iron composite layer and a second zinc-iron composite layer from outside to inside; wherein the content of iron in the first zinc-iron composite layer is lower than the content of iron in the second zinc-iron composite layer, so that a gradient coating with corrosion potential and hardness from low to high is formed, the first zinc-iron composite layer and the second zinc-iron composite layer both contain wear-resistant particles, and the wear-resistant particles form a wedge-shaped structure between the first zinc-iron composite layer and the second zinc-iron composite layer. The abrasion-resistant composite layer has good abrasion resistance and corrosion resistance, and the service capacity of metal components such as electric power fittings in the abrasion working condition can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surface treatment, and in particular to an anti-abrasion composite layer and a preparation method thereof. Background Art

[0002] As the most important basic material, carbon steel is widely used in industries such as electricity, communications, chemicals, and automobiles. For example, U-shaped rings, ball head hanging rings and other power fittings are exposed to various meteorological conditions all year round, and corrosion occurs all the time. Breeze vibration, dancing, icing, sub-span vibration, wire de-icing and jumping, etc., cause wear of line fittings to varying degrees, which makes power fittings have both corrosion and wear conditions. The commonly used hot-dip galvanized layer is neither corrosion-resistant nor wear-resistant in the coastal environment of high temperature, high humidity, high chlorine, and strong winds, resulting in frequent cases of abrasion failure of power fittings. On the other hand, people have put forward higher requirements on the environmental protection and cost of anti-abrasion materials. Therefore, the development of environmentally friendly and low-cost anti-abrasion layers with good performance has significant practical significance.

[0003] In order to improve the corrosion resistance of carbon steel components, researchers have studied zinc alloy coatings such as Zn-Ni, Zn-Co, and Zn-Fe. Among them, the Zn-Fe alloy layer has the lowest cost and is more environmentally friendly. Therefore, there are many studies on the deposition of Zn-Fe alloys with low and high iron contents. For example, CN104120466A, CN105442000A, CN109137016A, and CN1162571C prepared Zn-Fe alloy coatings with low iron content in acidic or alkaline baths, and CN117535744A and CN101545125A prepared Zn-Fe alloy coatings with iron contents of 12% to 18% and 17% to 20%, respectively. However, the composition of the Zn-Fe alloy has an important influence on its structure, which makes the performance of the alloy layer significantly different. A single Zn-Fe alloy coating is obviously difficult to meet the requirements of metal components such as power fittings in abrasive working conditions.

[0004] The researchers used composite deposition technology to improve the wear resistance of Zn-Fe coatings to a certain extent. Fan Yunying et al. added 20-60g / L of SiO2 particles with a particle size of 0.76μm to the acidic Zn-Fe system to prepare a ZnFe-SiO2 composite coating with an Fe content of about 10wt.% and a SiO2 content of up to 0.51wt.% (Fan Yunying et al., Effect of plating solution composition on the composition of Zn-Fe-SiO2 alloy composite coatings, Surface Technology, 2003, 32 (5): 53-55). The team also disclosed the preparation method of Zn-Fe-SiO2 composite coatings in acidic systems through CN1854351A, CN1854350A, CN1289717C, etc., and the electroplating process for preparing Zn-Fe-graphene composite coatings in alkaline systems was disclosed in CN109137016A and CN111636080A. However, in the prior art, due to the failure to take targeted measures to increase the content of micro-nano particles in the composite layer, the content of particles in the composite layer is extremely limited, so that the improvement of wear resistance is limited. Summary of the invention

[0005] In order to solve the above problems in the prior art, the purpose of the present invention is to provide an anti-wear composite layer and a preparation method thereof. The anti-wear composite layer has good wear resistance and corrosion resistance.

[0006] In order to achieve the above object, according to a first aspect of the present invention, there is provided an anti-wear composite layer, the anti-wear composite layer comprising, from the surface to the inside, a passivation layer, a first zinc-iron composite layer, and a second zinc-iron composite layer; wherein the iron content in the first zinc-iron composite layer is lower than the iron content in the second zinc-iron composite layer;

[0007] The Zn-Fe in the first zinc-iron layer is in η phase, and the Zn-Fe in the second zinc-iron layer is in γ phase;

[0008] The first zinc-iron composite layer and the second zinc-iron composite layer both contain wear-resistant particles, the particle size of the wear-resistant particles in the first zinc-iron composite layer is 10 nanometers to 10 micrometers, and the particle size of the wear-resistant particles in the second zinc-iron composite layer is 10 nanometers to 30 micrometers;

[0009] The thickness of the first zinc-iron composite layer and the second zinc-iron composite layer are independently 8 to 18 microns;

[0010] The composite amount of the wear-resistant particles in the anti-abrasion composite layer is 5-8 wt %.

[0011] The composite quantity measurement is carried out in the following way:

[0012] Peel off part of the composite coating and weigh the composite coating mass ( ), in a HNO3 aqueous solution with a volume ratio of 1:1 (wherein the concentrated nitric acid is a concentrated nitric acid aqueous solution with a mass concentration of 67%), the metal in the coating is completely dissolved, and after the wear-resistant particles are completely precipitated, they are separated and dried, and the mass of the particles in the coating is weighed ( ), and the composite amount is calculated from this .

[0013] The anti-wear composite layer of the present invention ensures the corrosion resistance of the coating to the substrate from many aspects. First, the passivation of the outer layer with low Fe content is used to form a passivation film to ensure that the three-layer structure has good corrosion resistance. Second, the potential difference between the coating and the steel substrate is gradually reduced by the gradient of increasing Fe content from the surface to the inside, so that it still has a certain corrosion resistance after the outer layer is gradually consumed. Third, the Zn-Fe layer acts as a sacrificial anode to provide cathodic protection to the substrate.

[0014] At the same time, the anti-wear composite layer of the present invention ensures the wear resistance of the coating to the substrate from many aspects. First, by utilizing the Fe content gradient in the coating from the surface to the inside, the component forms a passivation layer, a structural gradient from the η phase to the γ phase, and then forms a hardness gradient of the three-layer structure. Secondly, the hardness of the anti-wear composite layer is further improved by the dispersion strengthening effect of the wear-resistant particles. Finally, the friction coefficient of the anti-wear composite layer is greatly reduced by the wear-resistant particles, and the effect is enhanced by the mutual matching of the inner layer large-diameter wear-resistant particles and the outer layer small-diameter wear-resistant particles. In addition, the anti-wear composite layer of the present invention contains more wear-resistant particles, which can also provide better wear resistance.

[0015] In some preferred embodiments of the present invention, the iron content in the first zinc-iron layer is 0.03-1.0 wt %.

[0016] In some preferred embodiments of the present invention, the iron content in the second zinc-iron layer is 5-30wt%.

[0017] In some preferred embodiments of the present invention, the particle size of the wear-resistant particles in the first zinc-iron composite layer is 100 nanometers to 8 micrometers.

[0018] In some preferred embodiments of the present invention, the particle size of the wear-resistant particles in the second zinc-iron composite layer includes two types: 45 nanometers to 10 microns and 15 microns to 30 microns. The present invention preferably uses the mutual use of wear-resistant particles of different sizes, which is more conducive to improving the anti-wear effect of the multilayer structure. In addition to providing the same dispersion strengthening and self-lubricating effects as the small-size wear-resistant particles, the large-size wear-resistant particles also significantly improve the bonding strength between the first zinc-iron composite layer and the second zinc-iron composite layer through the wedge-shaped structure.

[0019] In some preferred embodiments of the present invention, the wear-resistant particles include diamond wear-resistant particles, silicon carbide wear-resistant particles, silicon dioxide wear-resistant particles, boron nitride wear-resistant particles, aluminum oxide wear-resistant particles, molybdenum sulfide wear-resistant particles, zirconium dioxide wear-resistant particles, titanium dioxide wear-resistant particles, silicon nitride wear-resistant particles, tungsten carbide wear-resistant particles, polytetrafluoroethylene wear-resistant particles, carbon fiber wear-resistant particles, carbon nanotube wear-resistant particles, graphite wear-resistant particles, and graphene wear-resistant particles. One or a combination of two or more.

[0020] Preferably, the wear-resistant particles include self-lubricating wear-resistant particles. More preferably, the self-lubricating wear-resistant particles include one or a combination of two or more of boron nitride wear-resistant particles, aluminum oxide wear-resistant particles, polytetrafluoroethylene wear-resistant particles, molybdenum sulfide wear-resistant particles, graphite wear-resistant particles, carbon nanotube wear-resistant particles, and graphene wear-resistant particles. The self-lubricating property of the above preferred wear-resistant particles is conducive to reducing the friction coefficient of the anti-wear composite layer and improving the wear resistance of the anti-wear composite layer.

[0021] In some preferred embodiments of the present invention, a substrate having an anti-wear composite layer is provided, wherein the anti-wear composite layer is the above-mentioned anti-wear composite layer, and the material of the substrate includes one or a combination of two or more of carbon steel, stainless steel, copper, and aluminum. In some preferred embodiments of the present invention, the first zinc-iron composite layer is prepared from a first solution. Based on the total volume of the first solution, the first solution includes: 8-15 g / L zinc oxide, 60-140 g / L sodium hydroxide, 1.5-15 g / L ammonium ferrous sulfate hexahydrate, 3-150 g / L (preferably 50-100 g / L) of the wear-resistant particles, 100-150 ml / L of a first multi-component complexing system, 80-120 ml / L of a combined brightener, 100-140 ml / L of a moving agent, 80-120 ml / L of a stabilizer, and 80-120 ml / L of an additive; wherein the first multi-component complexing system includes a first main complexing agent and a first auxiliary complexing agent, wherein the first main complexing agent includes one or a combination of more than two of sodium citrate, ammonium citrate, sodium salicylate, and pyridine; and the first auxiliary complexing agent includes sodium gluconate and / or triethanolamine.

[0022] In some preferred embodiments of the present invention, the second zinc-iron composite layer is prepared from a second solution. Based on the total volume of the second solution, the second solution includes: 8-15 g / L zinc oxide, 60-140 g / L sodium hydroxide, 10-40 g / L ammonium ferrous sulfate hexahydrate, 3-150 g / L of the wear-resistant particles, 100-150 ml / L of a second multi-component complexing system, 80-120 ml / L of a combined brightener, 80-120 ml / L of a displacement agent, 80-120 ml / L of a stabilizer, and 80-120 ml / L of an additive; wherein the second multi-component complexing system includes a second main complexing agent and a second auxiliary complexing agent, wherein the second main complexing agent includes one or a combination of more than two of tetraethylenepentamine, triethylenetetramine, and ethylenediamine, and the second auxiliary complexing agent includes sodium gluconate and / or triethanolamine.

[0023] In some preferred embodiments of the present invention, the wear-resistant particles in the second solution include two types, 45 nanometers to 10 microns and 15 microns to 30 microns, and the concentration of the wear-resistant particles with a particle size of 45 nanometers to 10 microns is 5 to 50 g / L, and the concentration of the wear-resistant particles with a particle size of 15 microns to 30 microns is 60 to 120 g / L. Selecting the two sizes of wear-resistant particles compounded according to the above concentrations is more conducive to using the wedge structure to improve the bonding strength between the first zinc-iron composite layer and the second zinc-iron composite layer.

[0024] The present invention utilizes the difference in the strength of the complexing ability of different multi-component complexing systems and the Fe 2+ When preparing the first zinc-iron composite layer with low Fe content, the concentration difference between Fe and Zn is selected. 2+ Strong complexation with Zn 2+ Weakly complexed complex systems (such as sodium citrate, ammonium citrate, etc.) and low Fe 2+ concentration; when preparing the second zinc-iron composite layer with high Fe content, use 2+ Weak complexation, with Zn 2+ Strong complexing system (such as tetraethylenepentamine, etc.), while using high Fe 2+ concentration.

[0025] The electrolyte solution of the present invention utilizes the antioxidant effect of the stabilizer and the complex system to Fe 2+ The complexation of Fe 2+ of oxidation.

[0026] In some preferred embodiments of the present invention, the solvent for preparing the solution is water.

[0027] In some preferred embodiments of the present invention, based on the total volume of the first multi-component complex system, in the first multi-component complex system, the concentration of the sodium citrate and / or ammonium citrate is 100-300 g / L (preferably 120-250 g / L), the concentration of the sodium salicylate is 18-180 g / L (preferably 24-120 g / L), the concentration of the pyridine is 0-180 g / L (preferably 0-120 g / L), the concentration of the sodium gluconate is 150-200 g / L (preferably 150-200 g / L), and the concentration of the triethanolamine is 100-300 mL / L (preferably 150-250 mL / L).

[0028] In the present invention, when the expression "the concentration of a certain component A and / or a certain component B is within a certain range" is used, it means that the certain component A and the certain component B are regarded as a group, and the "group" optionally contains a certain component A and / or a certain component B, and the overall concentration of the "group" is within the said range.

[0029] In some preferred embodiments of the present invention, based on the total volume of the second multi-component complex system, in the second multi-component complex system, the concentration of tetraethylenepentamine is 100-300mL / L (preferably 150-250mL / L), the concentration of triethylenetetramine is 0-200mL / L (preferably 0-150mL / L), the concentration of ethylenediamine is 0-200mL / L (preferably 0-150mL / L), the concentration of sodium gluconate is 100-300g / L (preferably 150-200g / L), and the concentration of triethanolamine is 50-200mL / L (preferably 100-150mL / L).

[0030] In some preferred embodiments of the present invention, the combined brightener includes one or a combination of two or more of benzylpyridinium carboxylate, vanillin, piperonal, heliotropin, polyethylene glycol, and butynediol.

[0031] In some preferred embodiments of the present invention, the displacement agent includes one or a combination of two or more of Mirapol WT, sodium vinyl sulfonate, sodium allyl sulfonate, and sodium tellurate.

[0032] In some preferred embodiments of the present invention, the stabilizer includes one or a combination of two or more of potassium sodium tartrate, sodium sulfite, manganese dichloride, and sodium ascorbate.

[0033] In some preferred embodiments of the present invention, the additive includes one or a combination of surfactants and rare earth salts; preferably, in the second solution, the additive includes thiazolidinethione. Preferably, the additive includes thiazolidinethione only when the substrate is an aluminum substrate.

[0034] Preferably, the surfactant comprises a cationic surfactant. Adding the cationic surfactant is conducive to adsorbing the cationic surfactant on the surface of the wear-resistant particles, improving the Zeta potential of the wear-resistant particles, and thus increasing the composite amount of the wear-resistant particles.

[0035] Preferably, the surfactant includes one or a combination of two or more of a quaternary ammonium salt surfactant and a pyridine surfactant. Preferably, the surfactant includes Chlorhexidine.

[0036] In some preferred embodiments of the present invention, the first multi-component complex system and / or the second multi-component complex system further comprises other additives; preferably, the other additives comprise glass balls, plastic balls or a combination of both.

[0037] Preferably, the particle size of the plastic balls is 1-4 mm, and the plastic material is preferably PVC or PA. The collision of the glass balls and the plastic balls on the surface of the coating is also beneficial to improving the compactness of the coating.

[0038] In some preferred embodiments of the present invention, the rare earth salt includes one or a combination of two or more of nitrates, acetates, sulfates, and chlorides of rare earth elements. Rare earth salt ions are easily adsorbed on the surface of electrodes and wear-resistant particles, thereby increasing the polarization resistance of the deposition system, promoting grain refinement, and further improving the hardness of the anti-wear composite layer. In addition, the cathode polarization of the rare earth salt and the wear-resistant particles makes the deposition layer more compact, which is beneficial to increasing the composite amount and also beneficial to improving the corrosion resistance of the anti-wear composite layer.

[0039] In some preferred embodiments of the present invention, the concentration of the benzylpyridinium carboxylate is 0.5-2 ml / L (preferably 0.6-1.2 mL / L), the concentration of one or a combination of more than two of the vanillin, piperonal, and heliotropin is 0.5-1.5 g / L (preferably 0.6-1 g / L), and the concentration of the polyethylene glycol and / or butynediol is 0.4-1.2 g / L (preferably 0.5-0.8 g / L).

[0040] In some preferred embodiments of the present invention, the concentration of Mirapol WT in the displacement agent is 10-20 g / L, the concentration of sodium vinyl sulfonate and / or sodium allyl sulfonate is 0.06-0.2 g / L (preferably 0.08-0.14 g / L), and the concentration of sodium tellurate is 0-0.16 g / L (preferably 0-0.1 g / L).

[0041] In some preferred embodiments of the present invention, the concentration of potassium sodium tartrate is 80-200 g / L (preferably 100-150 g / L), the concentration of sodium sulfite in the first solution is 0.25-1 g / L (preferably 0.4-0.8 g / L), the concentration of sodium sulfite in the second solution is 0.5-2 g / L (preferably 0.6-1.2 g / L), and the concentration of manganese dichloride and / or ascorbic acid is 0-50 g / L (preferably 0-30 g / L).

[0042] In some preferred embodiments of the present invention, the concentration of the surfactant is 0.4-8 g / L, the concentration of the rare earth salt is 0-0.25 mol / L, the concentration of the tetrahydrothiazolidinethione is 0-0.2 g / L, and the concentration of the glass balls and / or plastic balls is 40-250 particles / L.

[0043] Preferably, the concentration of the tetrahydrothiazolidinethione is 10-20 mg / L.

[0044] In some preferred embodiments of the present invention, the solution for preparing the passivation layer is recorded as the third solution. Based on the total volume of the third solution, the third solution includes 40-80 g / L chromium nitrate nonahydrate, 5-20 g / L sodium nitrate, 10-20 g / L sodium oxalate, 10-20 g / L sodium malonate, 1-2 g / L maleic anhydride, 5-8 g / L cobalt nitrate hexahydrate, and 3-5 mL / L amino silicon; the pH of the third solution is 2~2.5.

[0045] According to another aspect of the present invention, there is provided a method for preparing the above-mentioned anti-wear composite layer, which comprises:

[0046] The substrate is pretreated and used as a cathode;

[0047] Sequentially, electroplating and depositing on the cathode to obtain the second zinc-iron composite layer, and electroplating and depositing on the second zinc-iron layer to obtain the first zinc-iron composite layer, and obtaining an intermediate product; the electroplating and depositing is carried out under intermittent stirring conditions;

[0048] Passivating the intermediate product to obtain the anti-wear composite layer;

[0049] The anode includes one or a combination of two or more of stainless steel, nickel-plated steel and nickel plates.

[0050] Through intermittent stirring, wear-resistant particles can be transported to the cathode, and wear-resistant particles retained on the cathode surface can also be flushed. The flushing effect of stirring is obviously weakened during the intermittent stirring, and the inventors have found that the interfacial force between the new metal and the wear-resistant particles during composite deposition is conducive to the retention of wear-resistant particles on the cathode surface. The intermittent stirring can make full use of the retention effect of the interfacial force, thereby significantly increasing the content of wear-resistant particles in the composite layer. At the same time, the present invention adds rare earth ions, which can make the wear-resistant particles adsorb more positive charges, promote the movement of wear-resistant particles to the cathode and the retention on the cathode surface, thereby increasing the composite amount. In addition, in some embodiments of the present invention, a cationic surfactant is added, which is conducive to adsorption on the surface of wear-resistant particles, improves the Zeta potential of wear-resistant particles, and promotes the transmission and retention of wear-resistant particles to the cathode.

[0051] The intermittent stirring can be done by mechanical stirring, and air stirring is not suitable. Preferably, the stirring intensity is such that the wear-resistant particles are not easy to settle when the second zinc-iron composite layer is prepared, and the glass balls and / or plastic balls (if any) are preferably used to collide with the cathode surface when the first zinc-iron composite layer is prepared. The specific stirring intensity is adjusted according to the size of the tank, the particle size and density of the wear-resistant particles, etc.

[0052] In some preferred embodiments of the present invention, the conditions of intermittent stirring include: stirring for 10s~20s, intermittently for 5s~20s, and a stirring intensity of 0~3000rpm; in a preferred embodiment, the intermittent time when depositing the first zinc-iron composite layer is 10s~20s, the stirring intensity is 0~1500rpm, and the intermittent time when depositing the second zinc-iron composite layer is 5s~12s, and the stirring intensity is 0~3000rpm. When tribological properties are not required, stirring is not required, or only slight stirring is performed to remove bubbles on the electrode surface.

[0053] In some preferred embodiments of the present invention, the conditions for electroplating the second zinc-iron composite layer and depositing the first zinc-iron composite layer include: a cathode current density of 0.5 to 6 A / dm 2 , temperature is 10-40°C, time is 20-60 minutes; the deposition is carried out under intermittent stirring conditions.

[0054] In some preferred embodiments of the present invention, the conditions for the passivation treatment include: pH value of 2-2.5, temperature of 20-45° C., and time of 30-60 s.

[0055] Compared with hot-dip galvanizing, the present invention replaces the existing hot-dip galvanizing process at about 450°C with a Zn-Fe deposition process at room temperature, which has an obvious low-carbon advantage; compared with Zn-Ni deposition, the present invention replaces the existing hot-dip galvanizing process at about 450°C with a Zn-Fe deposition process at room temperature, which has an obvious low-carbon advantage; 2+ Replace Ni in Zn-Ni deposition 2+ , good environmental properties. The present invention also has the advantage of low cost, Zn 2+with Fe 2+ Widely available and inexpensive.

[0056] In some preferred embodiments of the present invention, the pretreatment method includes degreasing-water washing-rust removal-water washing-activation, with the purpose of obtaining a fresh substrate surface. Conventional treatment processes are sufficient, and 0.2-0.5% dilute nitric acid solution can be used for light emission.

[0057] Compared with the prior art, the beneficial technical effects of the present invention include:

[0058] The invention provides an environmentally friendly, low-cost anti-wear composite layer which has excellent wear resistance and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 A schematic structural diagram of the anti-abrasion composite layer of Example 4 of the present invention is shown. DETAILED DESCRIPTION

[0060] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0061] Example 1

[0062] A 10×20×2mm copper sheet was polished with #2000 sandpaper, washed with deionized water, and then subjected to degreasing-washing-rust removal-washing-activation pretreatment. After washing, it was used as a cathode in a charged tank in the second solution, and the anode was a nickel plate.

[0063] The second solution is composed of: 10g / L zinc oxide, 100g / L sodium hydroxide, 30g / L ammonium ferrous sulfate hexahydrate; the wear-resistant particles are 90g / L hexagonal boron nitride with a particle size of 30μm and 30g / L hexagonal boron nitride with a particle size of 3μm; the multi-component complex system is 20mL / L tetraethylenepentamine, 5mL / L triethylenetetramine, 20g / L sodium gluconate, and 10mL / L triethanolamine; the combined brightener is 0.1mL / L benzylpyridinium carboxylate, 80mg / L vanillin, and 60mg / L polyethylene glycol; the moving agent is Mirapol WT1.5g / L, sodium vinyl sulfonate 10mg / L, sodium tellurate 8mg / L; stabilizer: potassium sodium tartrate 15g / L, sodium sulfite 50mg / L, manganese dichloride 3g / L; additive: cerium sulfate 1g / L, chlorhexidine 0.04g / L; the balance is water.

[0064] During the electroplating process, the cathode current density is 3A / dm 2, the water bath temperature was 25°C, intermittent stirring was used, stirring for 10 seconds, intermittent for 10 seconds, and the stirring speed was 450rpm; after 30 minutes, a uniform second zinc-iron composite layer was obtained on the surface of the copper sheet, with a thickness of about 17 microns.

[0065] The EDS semi-quantitative analysis of the second zinc-iron composite layer without wear-resistant particles showed that the zinc content in the second zinc-iron composite layer was 70.2wt.%, the iron content was 21.4wt.%, and the remainder was other elements such as Cu. The hardness value tested by the microhardness tester was 662HV.

[0066] The composite amount was measured to be 7.8 wt.%. The composite amount was measured in the following manner:

[0067] Peel off part of the composite coating and weigh the composite coating mass ( ), heated in a HNO3 aqueous solution with a volume ratio of 1:1 of nitric acid and water to completely dissolve the metal in the coating, and after the wear-resistant particles are completely precipitated, separated and dried, the mass of the wear-resistant particles in the coating is weighed ( ), and the composite amount is calculated from this The weighing was carried out on a BS210S electronic balance from Sartorius, Germany, with an error of ±0.2 mg.

[0068] Example 2

[0069] A 10×20×2mm copper sheet was polished with #2000 sandpaper, washed with deionized water, and then subjected to degreasing-washing-rust removal-washing-activation pretreatment. After washing, it was used as a cathode in a charged tank in the first solution, and the anode was a nickel plate.

[0070] The first solution is composed of: 10g / L zinc oxide, 100g / L sodium hydroxide, 4g / L ammonium ferrous sulfate hexahydrate; 90g / L hexagonal boron nitride with a particle size of 3μm is used as the wear-resistant particles; 25g / L sodium citrate, 5g / L sodium salicylate, 15g / L sodium gluconate, and 10mL / L triethanolamine are used as the first multi-component complex system; 0.1mL / L benzylpyridinium carboxylate, 70mg / L piperonal, and 60mg / L butynediol are used as the combined brightener; 1.5g / L Mirapol WT, 10mg / L sodium vinyl sulfonate, and 8mg / L sodium tellurate are used as the positioning agent; 12g / L potassium sodium tartrate, 8mg / L sodium sulfite, and 1g / L manganese dichloride are used as the stabilizer; 2g / L cerium sulfate and 0.04g / L chlorhexidine are used as the rare earth salt in the additive; and the balance is water.

[0071] During the electroplating process, the cathode current density is 3A / dm 2; The stirring speed is 380rpm, and intermittent stirring is adopted, stirring for 10s and resting for 10s; the water bath temperature is 25℃; after 30 minutes, a bright and smooth composite coating with a thickness of 16 microns is obtained on the surface of the copper sheet.

[0072] The EDS semi-quantitative analysis of the coating without wear-resistant particles showed that the zinc content in the obtained coating was 91.6wt.%, the iron content was 0.6wt.%, and the remainder was other elements such as Cu.

[0073] The hardness value tested by microhardness tester is 168HV.

[0074] The composite amount was measured to be 5.2 wt.%.

[0075] Example 3

[0076] A 10×20×2mm copper sheet was polished with #2000 sandpaper, washed with deionized water, and then subjected to degreasing-washing-rust removal-washing-activation pretreatment. After washing, it was used as a cathode in a charged tank in the first solution, and the anode was a nickel plate.

[0077] The composition of the first solution was based on Example 2, except that 200 particles / L of PVC plastic balls with a diameter of 2 mm were added, the stirring intensity was increased to 520 rpm, and the other parameters were consistent with Example 2. The thickness of the obtained coating was 15 microns.

[0078] The EDS semi-quantitative analysis of the coating without wear-resistant particles showed that the zinc content in the coating was 90.8wt.%, the iron content was 0.9wt.%, and the remainder was other elements such as Cu.

[0079] The composite amount was measured to be 5.0 wt.%.

[0080] The hardness value of the microhardness tester is 192 HV, which is significantly improved compared with the hardness value of Example 2. It can be seen that the collision of the plastic ball has a positive effect on improving the hardness of the coating.

[0081] The coating obtained after deposition in the first solution is washed with water and then subjected to post-treatment steps such as light-washing-passivation-washing-sealing-drying to obtain the desired passivation layer. The solution used for the passivation treatment is: 60g / L chromium nitrate nonahydrate, 15g / L sodium nitrate, 10g / L sodium oxalate, 10g / L sodium malonate, 2g / L maleic anhydride, 6g / L cobalt nitrate hexahydrate, and 4mL / L amino silicon. The solution pH is adjusted to 2, the temperature is 30°C, and the passivation treatment time is 40s.

[0082] The unpassivated sample of Example 2 and the passivated sample of Example 3 were subjected to a 1000-hour neutral salt spray test. Red rust was visible on the former, but not on the latter.

[0083] Example 4

[0084] In this embodiment, a Q235 U-7 type U-shaped ring is used as a substrate to deposit an anti-wear composite layer.

[0085] Firstly, the pretreatment of degreasing, water washing, rust removal, water washing and activation is carried out. After water washing, it is used as a cathode in a charged tank in the second solution. The anode is a nickel plate. The deposition process is the same as in Example 1.

[0086] Then, it is directly used as a cathode in the first solution with charge in the tank, the anode is also a nickel plate, the deposition process is the same as that in Example 3, and the passivation treatment is performed according to the method in Example 3.

[0087] The total thickness of the anti-wear composite layer is 33 micrometers, wherein the thickness of the first zinc-iron composite layer is 16 micrometers, and the thickness of the second zinc-iron composite layer is 17 micrometers.

[0088] EDS semi-quantitative analysis was performed on the obtained coating without wear-resistant particles. The results showed that the zinc content in the obtained first zinc-iron composite layer was 96.1wt.%, the iron content was 1.0wt.%, and the balance was other elements such as C; the zinc content in the obtained second zinc-iron composite layer was 68.5wt.%, the iron content was 26.6wt.%, and the balance was other elements such as C.

[0089] The composite amount was measured to be 6.9 wt.%.

[0090] The hardness of the first zinc-iron composite layer tested by a microhardness tester is 207HV, and the hardness of the second zinc-iron composite layer is 649HV. No red rust was found in the sample after 1200 hours of neutral salt spray test.

[0091] Figure 1 This is a schematic diagram of the structure of the anti-wear composite layer prepared in Example 4 of the present invention. As the iron content increases from the surface to the inside, the potential difference between the anti-wear composite layer and the carbon steel substrate gradually decreases, thereby maintaining good corrosion resistance under the joint action of the passivation film, and at the same time, the evolution of the outer layer η phase to the inner layer γ phase greatly increases the hardness value, and the synergistic effect of the self-lubricating wear-resistant particles at different particle sizes together give the anti-wear layer excellent tribological properties.

[0092] Example 5

[0093] A 10×20×2mm 5052 aluminum test piece was polished with #2000 sandpaper, washed with deionized water, and then subjected to degreasing-washing-rust removal-washing-activation pretreatment. After washing, it was used as a cathode in a charged tank in the second solution, and the anode was a nickel plate.

[0094] The second solution is composed of: 10g / L zinc oxide, 100g / L sodium hydroxide, 30g / L ammonium ferrous sulfate hexahydrate; wear-resistant particles are 90g / L hexagonal boron nitride with a particle size of 30μm and 30g / L hexagonal boron nitride with a particle size of 3μm; the multi-component complex system is 20mL / L tetraethylenepentamine, 5mL / L triethylenetetramine, 20g / L sodium gluconate, and 10mL / L triethanolamine; the combined brightener is 0.1mL / L benzylpyridinium carboxylate, 80mg / L vanillin, and 60mg / L polyethylene glycol; the moving agent is Mirapol WT 1g / L, sodium vinyl sulfonate 10mg / L, sodium tellurate 8mg / L; stabilizer includes potassium sodium tartrate 15g / L, sodium sulfite 50mg / L, manganese dichloride 3g / L; rare earth salt in additive includes cerium sulfate 1g / L, chlorhexidine 0.04g / L, tetrahydrothiothione 20mg / L.

[0095] The cathode current density is 3A / dm 2 , water bath temperature 25℃, stirring speed 450rpm, stirring 10s, rest 10s. After 20 minutes, a well-bonded composite coating with a thickness of 10 microns was obtained on the surface of the 5052 aluminum test piece.

[0096] The EDS semi-quantitative analysis of the coating without wear-resistant particles showed that the zinc content in the coating was 80.4wt.%, the iron content was 14wt.%, and the balance was other elements such as Al. The hardness of the coating was measured to be 424HV. Because the coating was thin, the hardness value was affected by the aluminum substrate and was low, and the composite content was 4.6wt.%.

[0097] This embodiment illustrates that the composite coating of the present invention can be well applied on an aluminum substrate.

[0098] Comparative Example 1

[0099] A 10×20×2mm copper sheet was polished with #2000 sandpaper, washed with deionized water, and then subjected to degreasing-washing-rust removal-washing-activation pretreatment. After washing, it was used as a cathode in a charged tank in the second solution, and the anode was a nickel plate.

[0100] The second solution is composed of: 10g / L zinc oxide, 100g / L sodium hydroxide, 30g / L ammonium ferrous sulfate hexahydrate, 20mL / L tetraethylenepentamine, 5mL / L triethylenetetramine, 20g / L sodium gluconate, 10mL / L triethanolamine for the multi-component complex system, 0.1mL / L benzylpyridinium carboxylate, 80mg / L vanillin, 60mg / L polyethylene glycol for the combined brightener, 1.5g / L MirapolWT, 10mg / L sodium vinyl sulfonate, 8mg / L sodium tellurate for the moving agent, 15g / L potassium sodium tartrate, 50mg / L sodium sulfite, 3g / L manganese dichloride for the stabilizer, 0.004mol / L cerium sulfate and 0.04g / L chlorhexidine for the rare earth salt in the additive. The cathode current density is 3A / dm 2 , water bath temperature 25 ℃, after 30 minutes, the surface of the copper sheet will obtain a bright and smooth coating.

[0101] The semi-quantitative analysis results of EDS showed that the zinc content in the obtained coating was 75.2wt.%, the iron content was 23.1wt.%, and the rest was others. The hardness value tested by microhardness tester was 458HV.

[0102] Comparative Example 2

[0103] A 10×20×2mm copper sheet was polished with #2000 sandpaper, washed with deionized water, and then subjected to degreasing-washing-rust removal-washing-activation pretreatment. After washing, it was used as a cathode in a charged tank in the second solution, and the anode was a nickel plate.

[0104] The second solution is composed of: 10 g / L zinc oxide, 100 g / L sodium hydroxide, 30 g / L ammonium ferrous sulfate hexahydrate, 90 g / L hexagonal boron nitride with a particle size of 30 μm and 30 g / L hexagonal boron nitride with a particle size of 3 μm for wear-resistant particles, 20 mL / L tetraethylene pentamine, 5 mL / L triethylene tetramine, 20 g / L sodium gluconate and 10 mL / L triethanolamine for the multi-component complex system, 0.1 mL / L benzylpyridinium carboxylate, 80 mg / L vanillin and 60 mg / L polyethylene glycol for the combined brightener, and Mirapol WT for the moving agent. 1.5g / L, sodium vinyl sulfonate 10mg / L, sodium tellurate 8mg / L, stabilizer potassium sodium tartrate 15g / L, sodium sulfite 50mg / L, manganese dichloride 3g / L, rare earth salt additives cerium sulfate 1g / L, chlorhexidine 0.04g / L. Cathode current density is 3A / dm 2 , water bath temperature 25 ℃, continuous stirring, stirring speed 450rpm. After 30 minutes, the surface of the copper sheet obtained a bright and uniform composite coating with a coating thickness of 16 microns.

[0105] The hardness value tested by microhardness tester is 544HV.

[0106] The composite amount in the composite coating is 5.2wt.%.

[0107] Comparing Comparative Example 1 with Example 1, it can be found that in the present invention, the dispersion strengthening effect of the wear-resistant particles improves the microhardness of the composite coating, and the self-lubricating property of the hexagonal boron nitride wear-resistant particles also significantly improves the tribological properties of the material. Comparing Comparative Example 2 with Example 1, it can be found that the appropriate intermittent stirring method promotes the increase of the composite amount, and it is also significantly improved compared with the prior art, further enhancing the tribological properties of the material surface.

Claims

1. An anti-wear composite layer, characterized in that: The anti-wear composite layer includes a passivation layer, a first zinc-iron composite layer, and a second zinc-iron composite layer in order from the outside to the inside; wherein the iron content in the first zinc-iron composite layer is lower than the iron content in the second zinc-iron composite layer; The Zn-Fe in the first zinc-iron layer is in η phase, and the Zn-Fe in the second zinc-iron layer is in γ phase; The first zinc-iron composite layer and the second zinc-iron composite layer both contain wear-resistant particles, the particle size of the wear-resistant particles in the first zinc-iron composite layer is 10 nanometers to 10 micrometers, and the particle size of the wear-resistant particles in the second zinc-iron composite layer is 10 nanometers to 30 micrometers; The thickness of the first zinc-iron composite layer and the second zinc-iron composite layer are independently 8 to 18 microns; The composite amount of the wear-resistant particles in the anti-abrasion composite layer is 5-15wt%.

2. The anti-wear composite layer according to claim 1, characterized in that: The iron content in the first zinc-iron layer is 0.03-1.0wt%; and / or, The iron content in the second zinc-iron layer is 5-30wt%.

3. The anti-wear composite layer according to claim 1, characterized in that: The wear-resistant particles include diamond wear-resistant particles, silicon carbide wear-resistant particles, silicon dioxide wear-resistant particles, boron nitride wear-resistant particles, aluminum oxide wear-resistant particles, molybdenum sulfide wear-resistant particles, zirconium dioxide wear-resistant particles, titanium dioxide wear-resistant particles, silicon nitride wear-resistant particles, tungsten carbide wear-resistant particles, polytetrafluoroethylene wear-resistant particles, carbon fiber wear-resistant particles, carbon nanotube wear-resistant particles, graphite wear-resistant particles, graphene wear-resistant particles, or a combination of two or more thereof; and / or, the wear-resistant particles include self-lubricating wear-resistant particles; And / or, the self-lubricating wear-resistant particles include one or a combination of two or more of hexagonal boron nitride wear-resistant particles, aluminum oxide wear-resistant particles, polytetrafluoroethylene wear-resistant particles, molybdenum sulfide wear-resistant particles, graphite wear-resistant particles, carbon nanotube wear-resistant particles, and graphene wear-resistant particles.

4. A substrate having an anti-wear composite layer, characterized in that: The anti-wear composite layer is the anti-wear composite layer according to any one of claims 1 to 3, and the material of the substrate includes one or a combination of two or more of carbon steel, stainless steel, copper, and aluminum.

5. A method for preparing an anti-wear composite layer according to any one of claims 1 to 3, characterized in that include: After pretreatment, the substrate is used as a cathode; Sequentially, electroplating and depositing on the cathode to obtain the second zinc-iron composite layer, and electroplating and depositing on the second zinc-iron layer to obtain the first zinc-iron composite layer, and obtaining an intermediate product; the electroplating and depositing is carried out under intermittent stirring conditions; Passivating the intermediate product to obtain the anti-wear composite layer; The anode includes one or a combination of two or more of stainless steel, nickel-plated steel and nickel plates.

6. The preparation method according to claim 5, characterized in that: The conditions for electroplating and depositing the second zinc-iron composite layer and the first zinc-iron composite layer include: a cathode current density of 0.5 to 6 A / dm 2 , temperature of 10 to 40°C, time of 20 to 60 minutes; and / or, The passivation treatment conditions include: pH value of 2-2.5, temperature of 20-45° C., and time of 30-60 s.

7. The preparation method according to claim 5, characterized in that: The first zinc-iron composite layer is prepared from a first solution. Based on the total volume of the first solution, the first solution includes: 8-15 g / L zinc oxide, 60-140 g / L sodium hydroxide, 1.5-15 g / L ammonium ferrous sulfate hexahydrate, 3-150 g / L wear-resistant particles, 100-150 ml / L of a first multi-component complexing system, 80-120 ml / L combined brightener, 100-140 ml / L moving agent, 80-120 ml / L stabilizer, and 80-120 ml / L additive; wherein the first multi-component complexing system includes a first main complexing agent and a first auxiliary complexing agent, wherein the first main complexing agent includes one or a combination of two or more of sodium citrate, ammonium citrate, sodium salicylate, and pyridine; the first auxiliary complexing agent includes sodium gluconate and / or triethanolamine; and / or, The second zinc-iron composite layer is prepared from a second solution. Based on the total volume of the second solution, the second solution includes: 8-15 g / L zinc oxide, 60-140 g / L sodium hydroxide, 10-40 g / L ammonium ferrous sulfate hexahydrate, 3-150 g / L wear-resistant particles, 100-150 ml / L of a second multi-component complexing system, 80-120 ml / L combined brightener, 80-120 ml / L displacement agent, 80-120 ml / L stabilizer, and 80-120 ml / L additives; wherein the second multi-component complexing system includes a second main complexing agent and a second auxiliary complexing agent, wherein the second main complexing agent includes one or a combination of more than two of tetraethylenepentamine, triethylenetetramine, and ethylenediamine, and the second auxiliary complexing agent includes sodium gluconate and / or triethanolamine; and / or, Based on the total volume of the first multi-component complex system, in the first multi-component complex system, the concentration of sodium citrate and / or ammonium citrate is 100-300 g / L, the concentration of sodium salicylate is 18-180 g / L, the concentration of pyridine is 0-180 g / L, the concentration of sodium gluconate is 150-200 g / L, and the concentration of triethanolamine is 100-300 mL / L; and / or, Based on the total volume of the second multi-component complex system, in the second multi-component complex system, the concentration of tetraethylenepentamine is 100-300mL / L, the concentration of triethylenetetramine is 0-200mL / L, the concentration of ethylenediamine is 0-200mL / L, the concentration of sodium gluconate is 100-300g / L, and the concentration of triethanolamine is 50-200mL / L.

8. The preparation method according to claim 7, characterized in that: The combined brightener comprises one or a combination of two or more of benzylpyridinium carboxylate, vanillin, piperonal, heliotropin, polyethylene glycol, and butynediol; and / or, The displacement agent includes one or a combination of two or more of Mirapol WT, sodium vinyl sulfonate, sodium allyl sulfonate, and sodium tellurate; and / or, The stabilizer includes one or a combination of two or more of potassium sodium tartrate, sodium sulfite, manganese dichloride, and sodium ascorbate; and / or, The additive includes one or a combination of two or more of a surfactant and a rare earth salt; in the second solution, the additive includes tetrahydrothiazolidinethione; and / or, The first multi-component complex system and / or the second multi-component complex system further include other additives; the other additives include glass balls, plastic balls or a combination of the two.

9. The preparation method according to claim 8, characterized in that: The concentration of the benzylpyridinium carboxylate is 0.5-2 ml / L, the concentration of one or a combination of two or more of vanillin, piperonal and heliotropin is 0.5-1.5 g / L, and the concentration of the polyethylene glycol and / or butynediol is 0.4-1.2 g / L; and / or, The concentration of Mirapol WT is 10-20 g / L, the concentration of sodium vinyl sulfonate and / or sodium allyl sulfonate is 0.06-0.2 g / L, and the concentration of sodium tellurate is 0-0.16 g / L; and / or, The concentration of potassium sodium tartrate is 80-200 g / L, the concentration of sodium sulfite in the first solution is 0.25-1 g / L, the concentration of sodium sulfite in the second solution is 0.5-2 g / L, and the concentration of manganese dichloride and / or ascorbic acid is 0-50 g / L; The concentration of the surfactant is 0.4-8 g / L, the concentration of the rare earth salt is 0-0.25 mol / L, and the concentration of the tetrahydrothiazolidinethione is 0-0.2 g / L; The concentration of the glass balls and / or the plastic balls is 40-250 particles / L.

10. The preparation method according to claim 5, characterized in that: The solution for preparing the passivation layer is recorded as the third solution. Based on the total volume of the third solution, the third solution includes 40-80 g / L chromium nitrate nonahydrate, 5-20 g / L sodium nitrate, 10-20 g / L sodium oxalate, 10-20 g / L sodium malonate, 1-2 g / L maleic anhydride, 5-8 g / L cobalt nitrate hexahydrate, and 3-5 mL / L amino silicon; the pH of the third solution is 2~2.5.

Citation Information

Patent Citations

  • Bright corrosion resisting zinc-iron alloy plating process

    CN101545125A

  • Weak acid chloride electroplating solution used for neodymium iron boron electroplating of zinc-iron alloy and preparation method

    CN104120466A

  • Alkaline zinc-iron alloy electroplate liquid, preparation method and electroplating process

    CN105442000A

  • Alkaline graphene zinc-iron alloy electroplating liquid, preparation method and electroplating technology

    CN109137016A

  • Alkaline graphene zinc-iron alloy electroplating solution and electroplating process thereof

    CN111636080A